The level of moral dependence among a sample of students with learning disabilities in English from the point of view of their teachers - Mohamad Ahmad Saleem Khasawneh (Open Science LLC, 2021)
This study explored the level of moral dependence among a sample of students with learning disabilities in English from the point of view of their teachers in Irbid Governorate, Jordan. The study population consisted of (60) male and female teachers who teach learning disabilities in English language for the academic year 2020/2021. The study sample consisted of (30) male and female teachers. The description method was used, and to achieve the objectives of the current research, the study instrument was developed, which consisted of (45) items. The results showed that the level of moral dependency among people with learning difficulties in the English language was high. The results were discussed in light of the theoretical framework of the study and the results of previous studies and research in the field. Then, a set of educational recommendations and proposed studies were presented.